Respostas

2013-08-08T14:33:10-03:00
4x(x+6)-x²=5x²
4x
²+24x-x²=5x²
3x
²+24x=5x²
24x=2x
²
2x
²-24x=0
x(2x-24)=0
x=0 ou 2x-24=0
2x=24
x=12
20 4 20
2013-08-08T14:48:26-03:00
4x(x+6)-x²=5x²
4x²+-x²-5x²+24x
-2x+24x

delta= b²-4.a.c
delta= 24²(-4).(-2).0
delta= 576

-b+- raiz de delta
--------------------------
           2.a

-24+- raiz de 576
----------------------------
          2.(-2)

-24+- 24
-------------
       -4
 x'= -24 + 24                
     --------------     = 0      
            -4

x"= -24 -24           -48    
     ------------     = -----------  =  12
           -4                -4

2 5 2